The Role of United Nations in Economic and Social Development of Iraq Between 2003-2021 - DALAL, SARA (İstanbul Kültür Üniversitesi, 2023)
Ending several years of conflict between many different parties in Iraq, the Sunni, Shi'a and probably between Persians and Arabs which caused humanitarian and social tragedy in several states, describes as a platform of international terrorism and disturbance in oil production from the most significant area that affecting the global oil markets, so because of these factors the UN played a serious role that is necessary and justified even if we can't guarantee the success. In this research by using Secondary source in order to describe the significant role of UN in developing economic and social sectors of Iraq between 2003 until 2021. The year 2003 was a turning point on the political level in Iraq, which witnessed a series of changes and challenges in particular on the economic and social situations, so the questions are: how did the Iraqi people adapt to the difficult conditions? How the UN played a significant role through its relationship with the Iraqi Government? However, the development of economic and social conditions by the UN played a role in revealing many details.
Yılları Arasında Irak'ın Ekonomik ve Sosyal Gelişiminde Birleşmiş Milletlerin Rolü 2003-2021
▪ Yüksek lisans tezi.
Keywords: Economic; Social; United Nations; Development; Rights; Security Council